2010
DOI: 10.1111/j.1467-6427.2009.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Family therapists in trauma‐response teams: bringing systems thinking into interdisciplinary fieldwork

Abstract: Attention to the mental health facets of disaster‐preparedness and trauma‐response teams has increased considerably over the past decade. As family therapists take part in these efforts, they bring with them a worldview that adds valuable contributions to the nature in which fieldwork is conducted and the manners in which interdisciplinary teams function on the ground. In this article, we present how systems thinking sensitizes trauma workers to a variety of clinical presentations and biopsychosocial complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Increasing attention is paid to the role of these factors in the development and maintenance of a productive therapeutic alliance. 11,17 As an individual, the physician absorbs the general principles and particular features of the culture of medicine as practised in their location and filtered through their own cultural background. The patie t s ultu al a kg ou d i gs ith it o eptio s of t ust, espe t fo autho it figu es, dignity, self-image, self-esteem, and family-nourished beliefs and attitudes that the physician needs to appreciate to develop a positive and productive therapeutic alliance.…”
Section: Culture and Patient Carementioning
confidence: 99%
“…Increasing attention is paid to the role of these factors in the development and maintenance of a productive therapeutic alliance. 11,17 As an individual, the physician absorbs the general principles and particular features of the culture of medicine as practised in their location and filtered through their own cultural background. The patie t s ultu al a kg ou d i gs ith it o eptio s of t ust, espe t fo autho it figu es, dignity, self-image, self-esteem, and family-nourished beliefs and attitudes that the physician needs to appreciate to develop a positive and productive therapeutic alliance.…”
Section: Culture and Patient Carementioning
confidence: 99%
“…One of the purposes of the present study was to pinpoint important information that would inform mental health intervention with mothers in disaster contexts. In line with the emphasis on mobilising resources in a systemic way, Wells (2006), Landau, Mittal, and Wieling (2008), and Mendenhall and Berge (2010) discussed the importance of treating trauma using a systemic and contextualised lens. Wells (2006) indicated that treating a family system as a whole is important because trauma faced by one family member will surely reverberate through the system.…”
Section: Discussionmentioning
confidence: 99%
“…Family therapy is relatively new in the field of traumatology, which has previously focused more extensively on individual responses (Mendenhall and Berge, 2010). However, the family plays a powerful role in providing strength and resilience in responding to crises such as trauma (Walsh, 1998).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…This can be accomplished by identifying individual strengths and examples of resilience in family members and highlighting them as beacons of success (Boss et al, 2003), which can foster a climate in which hope can be stimulated that is essential for recovery (Walsh, 2007). Multi-systemic approaches to working with families and communities after traumatic events are now being advocated (Mendenhall and Berge, 2010;Walsh, 2007). As with any victim, ways of empowerment must be found.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation